Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.123
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Word Lexical Simplification

Abstract: In this work we propose the task of multi-word lexical simplification, in which a sentence in natural language is made easier to understand by replacing its fragment with a simpler alternative, both of which can consist of many words. In order to explore this new direction, we contribute a corpus (MWLS1), including 1462 sentences in English from various sources with 7059 simplifications provided by human annotators. We also propose an automatic solution (Plainifier) based on a purpose-trained neural language m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Currently, the best performing LS system for English is the LSBert system (Qiang et al, 2020a ), which uses pre-trained transformer language model BERT (Devlin et al, 2019 ) and a masking technique for finding suitable simplifications for complex words. This approach was further extended by Przybyła and Shardlow ( 2020 ) to build a multi-word LS system for English. The LSBert system (Qiang et al, 2020a ) and our adaptation of it to Spanish and Portuguese will be described in more details in Section 4.2.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, the best performing LS system for English is the LSBert system (Qiang et al, 2020a ), which uses pre-trained transformer language model BERT (Devlin et al, 2019 ) and a masking technique for finding suitable simplifications for complex words. This approach was further extended by Przybyła and Shardlow ( 2020 ) to build a multi-word LS system for English. The LSBert system (Qiang et al, 2020a ) and our adaptation of it to Spanish and Portuguese will be described in more details in Section 4.2.…”
Section: Related Workmentioning
confidence: 99%
“…frequency, vectorbased semantic similarity, and/or language model probability. Studies using LSBert (Przybyła and Shardlow, 2020;Štajner et al, 2022) have shown that the approach could easily be adapted to other languages and still achieve state-of-the-art results.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, simplification systems have focused on the use of transformer architecture to identify appropriate replacements for a given word (Qiang et al, 2021). This can be applied at a single or multi-word level (Przybyła and Shardlow, 2020).…”
Section: Related Workmentioning
confidence: 99%